2005
DOI: 10.1038/sj.jcbfm.9600062
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection against Focal Ischemic Brain Injury by Inhibition of c-Jun N-Terminal Kinase and Attenuation of the Mitochondrial Apoptosis-Signaling Pathway

Abstract: c-Jun N-terminal kinase (JNK) is an important stress-responsive kinase that is activated by various forms of brain insults. In this study, we have examined the role of JNK activation in neuronal cell death in a murine model of focal ischemia and reperfusion; furthermore, we investigated the mechanism of JNK in apoptosis signaling, focusing on the mitochondrial-signaling pathway. We show here that JNK activity was induced in the brain 0.5 to 24 h after ischemia. Systemic administration of SP600125, a small mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(214 citation statements)
references
References 77 publications
7
203
1
Order By: Relevance
“…For example, the attenuation of hepatic I/R injury by a p38 MAPK inhibitor identifies p38 M APK as a therapeutic target in I/R injury (Kobayashi et al, 2002). JNK has also been suggested as a therapeutic target in reperfusion injury of major organs, such as the brain (Gao et al, 2005) and the lung (Ishii et al, 2004) because it was found that chemical JNK inhibitors attenuate reperfusion injury in these organs. Uehara et al, (2005) recently reported that several novel JNK inhibitors successfully attenuated hepatic I/R injury and increased the survival rate of rats subjected to partial hepatic I/R and resectioning of the remaining non-ischemic lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the attenuation of hepatic I/R injury by a p38 MAPK inhibitor identifies p38 M APK as a therapeutic target in I/R injury (Kobayashi et al, 2002). JNK has also been suggested as a therapeutic target in reperfusion injury of major organs, such as the brain (Gao et al, 2005) and the lung (Ishii et al, 2004) because it was found that chemical JNK inhibitors attenuate reperfusion injury in these organs. Uehara et al, (2005) recently reported that several novel JNK inhibitors successfully attenuated hepatic I/R injury and increased the survival rate of rats subjected to partial hepatic I/R and resectioning of the remaining non-ischemic lobes.…”
Section: Discussionmentioning
confidence: 99%
“…SP600125, a reversible ATP-competitive inhibitor, selectively inhibits JNK activity (Bennett et al, 2001), reduces ischemia-reperfusion injury in the brain (Gao et al, 2005) and the lungs (Ishii et al, 2004), and protects hepatocytes from apoptosis due to TNF- (Marderstein et al, 2003). Therefore, we attempted to determine whether SP600125 attenuates hepatic I/R injury in vivo using a partial hepatic I/R model in mice.…”
Section: Introductionmentioning
confidence: 99%
“…4 Inhibition of either activated JNK or p38 MAPK, by drugs or by gene therapy, can protect against cell death after ischemia. [5][6][7] Stress-activated protein kinase signaling pathways contain various checkpoints for regulation. Many studies have demonstrated that phosphorylation of upstream kinases is significant in regulating the signaling cascade.…”
Section: Introductionmentioning
confidence: 99%
“…However, we found a reproducible upregulation of the proapoptotic BH3-only genes Bik, Bim, and Noxa by cerebral ischemia. The induction of Bim by cerebral ischemia has been reported previously (Shibata et al, 2002;Gao et al, 2005).…”
Section: Mandola 2001mentioning
confidence: 99%